Lateral Infiltration Capacity of Pervious Concrete and Its Performance as Pavement Curb - Kamarul Zaman, A.B. (American Society of Civil Engineers (ASCE), 2022)
Flash flood occurrence on roads due to heavy rainfalls is reported frequently. Ponded or accumulated water on roads is a nuisance to traffic users if not properly conveyed. This paper introduces a pervious concrete pavement curb technology to address such problem. This technology is able to infiltrate ponding water into pervious curbs placed along the road. The pervious concrete mix design was adapted from the established literature. The main intention of the paper was to understand the hydraulic capacity of the pervious curb under varying lateral flows. Experimental testing was carried in the laboratory using a fabricated roadway flume. A testing tool to measure the lateral infiltration capacity was introduced. The capacity of the pervious curb was compared with the performance of roadways designed with grate inlets. The results showed that placing a pervious curb next to an existing grate inlet enhanced the performance better than using the curb alone. The pervious concrete pavement curb technology is believed to provide cheaper solutions to managing floods during rainfall events. Â© 2021 American Society of Civil Engineers.